2014
DOI: 10.1186/2052-4374-26-9
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function decline in firefighters and non-firefighters in South Korea

Abstract: ObjectivesThe purpose of this study was to evaluate and compare changes to pulmonary function among firefighters and non-firefighters who were exposed to harmful substances in their work environments.MethodsFirefighters (n = 322) and non-firefighters (n = 107) in Daegu who received a pulmonary function test in 2008 and 2011 as well as a regular health examination were included. Repeated measures ANOVA was performed to evaluate the pulmonary function of the two groups over the three-year period.ResultsAfter adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…It implies that as the years of service increases, the lung function parameters decreases proportionately. Our finding is similar to other previously published studies which have also shown a decline in lung function as duration of service increases [4,5,9,10] . Unger et al, demonstrated a trend towards an increased rate of volume loss in the FVC and FEV1 as years progressed, among the fire fighters [11].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It implies that as the years of service increases, the lung function parameters decreases proportionately. Our finding is similar to other previously published studies which have also shown a decline in lung function as duration of service increases [4,5,9,10] . Unger et al, demonstrated a trend towards an increased rate of volume loss in the FVC and FEV1 as years progressed, among the fire fighters [11].…”
Section: Discussionsupporting
confidence: 93%
“…The pioneering studies on lung function among firefighters were conducted in Boston in the 1970s [3]. Since then many studies have been conducted to assess the acute and chronic effects of smoke on lung function [4][5][6][7][8][9][10]. Acute effects on the lungs have well been documented in these studies.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon monoxide, cyanide, low oxygen concentration, isocyanides, and nitrogen dioxide cause harm to the bronchi and alveoli leading to acute respiratory dysfunction (20). In addition, exposure to hydrochloric acid, nitrogen dioxide, sulphur dioxide, aldehydes, and ammonium cause inflammatory responses in the neutrophils that lead to elevated respiratory sensitivity, decreased respiratory function, harm to the respiratory conduction system in further cases causing chronic bronchitis, bronchiectasis, asthma, and pulmonary fibrosis (21).…”
Section: Controlmentioning
confidence: 99%
“…Another less common effect from isocyanate exposure is hypersensitivity pneumonitis, an inflammation of the alveoli caused by inhaled isocyanate particles (Lockey et al 2015;Vandenplas et al 1992). In terms of lowdose and chronic exposure, it has been suggested that isocyanates, together with carbon monoxide, cyanide, nitrogen dioxide as well as a low oxygen concentration can cause irreversible damage to the bronchi and alveoli and acute respiratory function (Choi et al 2014). A summary of human health effects for individual isocyanates are presented in Table 1.…”
Section: Impact On Human Healthmentioning
confidence: 99%